Plataforma administrativa para el fomento empresarial: Plan parcial agroindustrial frutícola Mosquera 2050 (2016)
The agroindustrial partial plan approach fruit, take advantage of the strength of the sector, to generate added value and export products and domestic marketing, action units. which support and complement each other for the proper functioning of the partial plan are determined. The units that develop are the fruit treatment plant, the second and complementary is the processing plant waste and composting, educational and research facilities, finally the unit that leads these processes, the administrative unit of urban development and business management.